Pengenalan Gerakan “KOSPEL TINGGI” pada Siswa untuk Menumbuhkan Giat Literasi dan Menghasilkan Karya di UPTD SMPN 2 Pangarengan - Ainul Fajar; Desiyanto, Jatim; Rohisotul Laily; M. Farid (EDUPEDIA Publisher, 2024)
The low quality of literacy levels at SMPN 2 Pangarengan is inseparable from the limited teaching staff and ineffective learning for students. Complete literacy education facilities and infrastructure cannot be used optimally, this is influenced by environmental factors which cause the representation of work in literacy activities to be less visible, Therefore, it is necessary to introduce new learning in the education system in this activity, the target is SMPN 2 Pangarengan, the activities carried out are by optimizing literacy activities by holding regular activities such as book discussion groups, literacy workshops, and monthly meetings to discuss selected books, methods carried out, There are three stages of implementation in the context of introducing literacy to improve giyat in producing a work at SMPN 2 Pangarenga, namely 1). habituation, 2). Development, 3). Learning. This activity reflects on the planning activities that have been matched by the STKIP PGRI Sampang KKN team. The result achieved is that this community service produces a written work in the form of an anthology of poetry which is packaged into a book about